1971
DOI: 10.1161/01.cir.44.6.1022
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Right Bundle-Branch Block in Patients Undergoing Total Correction of Tetralogy of Fallot

Abstract: The electrocardiographic (ECG) pattern of right bundle-branch block (RBBB) occurs routinely in patients after open-heart surgery for tetralogy of Fallot (TF). To determine the etiology of the RBBB pattern, 14 patients with TF, seven with ventricular septal defects (VSD), and one with pulmonary stenosis (PS) were studied during and after cardiac surgery. Bipolar electrograms from 10 selected right ventricular epicardial sites were recorded simultaneously with an ECG. Records were obtained before and immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 24 publications
(1 reference statement)
2
20
0
Order By: Relevance
“…The AH interval was prolonged in two patients, and the HV interval was prolonged in three. Delayed right ventricular apex activation was observed in 22 patients, consistent with "central" right bundle branch block.27 28 Symptomatic arrhythmias/late death. None (table 3).…”
Section: Resultsmentioning
confidence: 98%
“…The AH interval was prolonged in two patients, and the HV interval was prolonged in three. Delayed right ventricular apex activation was observed in 22 patients, consistent with "central" right bundle branch block.27 28 Symptomatic arrhythmias/late death. None (table 3).…”
Section: Resultsmentioning
confidence: 98%
“…If and when such injury to the proximal part of the right bundle branch occurs, it might not always be detected with the epicardial recording technique previously used, 13 25 we feel that the disruption of the right bundle branch at the level of the moderator band is of clinical importance. This is so mainly because it is a major fascicle of the right bundle branch and disruption occurs prior to its insertion into right ventricular myocardium.…”
Section: Resultsmentioning
confidence: 94%
“…In their study Gelband et al 13 demonstrated that, on completion of the ventriculotomy, right ventricular activation was delayed at sites lateral to the ventriculotomy. Since activation time did not change medial to the ventriculotomy following infundibular resection and VSD closure, they assumed "that no further injury occurred with further procedures.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations